High-performance and environmentally stable planar heterojunction perovskite solar cells based on a solution-processed copper-doped nickel oxide hole-transporting layer - Kim, Jong H (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.